Antifungal Studies of Volatile Constituents of Boswellia serrata - Gangwal, M.L.; Vardhan, D.K. (Asian Journal of Chemistry, 2010)
The essential oil of Boswellia serrata was extracted by hydro-distillation with a yield of 0.6% and tested against several human pathogenic and plant pathogenic fungi.